Molecular Characterization of the NADPH Oxidase Complex in the Ergot Fungus Claviceps purpurea: CpNox2 and CpPls1 Are Important for a Balanced Host-Pathogen Interaction - Janine Schürmann; Dagmar Buttermann; Andrea Herrmann; Sabine Giesbert; Paul Tudzynski (Molecular Plant-Microbe Interactions, 2013)
Reactive oxygen species producing NADPH oxidase (Nox) complexes are involved in defense reactions in animals and plants while they trigger infection-related processes in pathogenic fungi. Knowledge about the composition and localization of these complexes in fungi is limited; potential components identified thus far include two to three catalytical subunits, a regulatory subunit (NoxR), the GTPase Rac, the scaffold protein Bem1, and a tetraspanin-like membrane protein (Pls1). We showed that, in the biotrophic grass-pathogen Claviceps purpurea, the catalytical subunit CpNox1 is important for infection. Here, we present identification of major Nox complex partners and a functional analysis of CpNox2 and the tetraspanin CpPls1. We show that, as in other fungi, Nox complexes are important for formation of sclerotia; CpRac is, indeed, a complex partner because it interacts with CpNoxR, and CpNox1/2 and CpPls1 are associated with the endoplasmatic reticulum. However, unlike in all other fungi, Δcppls1 is more similar to Δcpnox1 than to Δcpnox2, and CpNox2 is not essential for infection. In contrast, Δcpnox2 shows even more pronounced disease symptoms, indicating that Cpnox2 controls the infection process and moderates damage to the host. These data confirm that fungal Nox complexes have acquired specific functions dependent of the lifestyle of the pathogen.